INTERYER VA EKSTERYER DIZAYNIDA GRAFIK NAQSHLARNI MUHANDISLIK GRAFIKASI ASOSIDA MODELLASHTIRISH USLUBLARI (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article discusses the issues of creating graphic patterns in interior and exterior design, modeling them based on engineering graphics and improving them based on artistic and ergonomic principles. The application of the principles of compositional balance, proportions, rhythm and symmetry in the process of graphic modeling is scientifically based.